Reliability and validity of tethered swimming lactate minimum test and their relationship with performance in young swimmers - Kalva-Filho, C. A.; Toubekis, A.; Moura Zagatto, A. M.; Sanchez Ramos da Silva, A.; Paulo Loures, J.; Zapaterra Campos, E.; Papoti, M. (Pediatric Exercise Science, 2018)
Purpose: To test the reliability and validity of tethered swimming lactate minimum test in young swimmers. Methods: Lactate minimum test was performed twice to test the reliability (experiment 1; n=13). In addition, the validity was investigated through lactate minimum test relationships with tethered swimming lactate threshold and peak force obtained during graded exercise test (experiment 2; n=11). Finally, the correlations with mean speeds observed during 200-m (s200m) and 30-minute continuous efforts (s30min) were also analyzed (experiment 3; n=15). In all experiments, the lactate minimum test began with 3-minute all-out effort to induce lactatemia, followed by an exhaustive graded exercise test. Results: The lactate minimum intensity and mean force during the entire 3-minute all-out effort (MF) showed high reliability (coefficient of variation<8.9% and intraclass correlation coefficient>.93). The lactate minimum intensity was not different compared with lactate threshold (P=.22), presenting high correlations (r=.92) and agreement (95% limits of agreement=±7.9 N). The mean force during the entire 3-minute all-out effort was similar to peak force obtained during graded exercise test (P=.41), presenting significant correlations (r=.88) and high indices of agreement (95% limits of agreement=±11.3 N). In addition, lactate minimum test parameters correlated both with mean speeds observed during 200-m (r>.74) and 30-minute continuous efforts (r>.70). Conclusion: Thus, tethered swimming lactate minimum test can be used for training recommendations and to monitor aerobic adaptations in young swimmers.